Ontogenetic development of pompano Trachinotus ovatus - Ma, Zhenhua; Yu, Gang.; Qin, Jian Guang (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book highlights the ontogenetic development of larval T. ovatus, provides a comprehensive overview of larval rearing of this species. It focuses on the physiological and molecular changes during the early ontogeny of T. ovatus and hatchery and nursery practices. The first seven chapters update the recent development in the hatchery technology in T. ovatus, including feed and feeding, environmental manipulation, hatchery management, and fingerlings in transportation. Chapter eight and onwards decode the possible molecular mechanisms underlying fish development and response to environmental changes and discuss the transcription and expressions of growth and development-related genes in T. ovatus. The last chapters discuss the functional feed additives to the diet and antibiotic usage of T. ovatus juveniles. This book is a valuable resource for researchers, practitioners and students in the aquaculture industry and related fields.
1 Ontogenetic development of the digestive system in golden pompano Trachinotus ovatus -- 2 Food consumption, ingestion and selectivity of golden pompano Trachinotus ovatus larvae, under various rotifer densities -- 3 Weaning regimes for golden pompano Trachinotus ovatus larvae -- 4 Skeleton development and malformation of hatchery-reared golden pompano Trachinotus ovatus -- 5 Nutrition and temperature regulate rearing performance of golden pompano Trachinotus ovatus larvae -- 6 Physical responses of golden pompano Trachinotus ovatus to rearing salinity -- 7 Physiological responses of golden pompano Trachinotus ovatus larvae fingerlings in transportation -- 8 Transcriptional response of golden pompano Trachinotus ovatus larvae to temperature -- 9 IGF genes in golden pompano Trachinotus ovatus larvae -- 10 High water temperature induces jaw deformity and bone morphogenetic proteins (BMPs) gene expression in golden pompano Trachinotus ovatus larvae -- 11 Twist gene in golden pompano Trachinotus ovatus larvae -- 12 Intestinal fatty acid binding protein gene (I-FABP) in golden pompano Trachinotus ovatus larvae -- 13 Effects of water temperature and nutritional manipulation on the expression of liver-type fatty acid-binding protein (L-FABP) gene in golden pompano Trachinotus ovatus larvae -- 14 Follistatin-related protein gene in golden pompano Trachinotus ovatus larvae -- 15 Functional feed additives to the diet of golden pompano Trachinotus ovatus juveniles -- 16 The intestine microbiota community and enzyme activity in Trachinotus ovatus after short-time antibiotic bath administration.
Keywords: Vertebrates; Developmental biology; Cytology; Vertebrate Zoology; Developmental Biology and Stem Cells; Cell Biology